Aqueductal Stroke Volume: Comparisons with Intracranial Pressure Scores in Idiopathic Normal Pressure Hydrocephalus - Ringstad, G.; Emblem, K.E.; Geier, O.; Alperin, N.; Eide, P.K. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Aqueductal stroke volume from phase-contrast MR imaging has been proposed for predicting shunt response in normal pressure hydrocephalus. However, this biomarker has remained controversial in use and has a lack of validation with invasive intracranial monitoring. We studied how aqueductal stroke volume compares with intracranial pressure scores in the presurgical work-up and clinical score, ventricular volume, and aqueduct area and assessed the patient's response to shunting.MATERIALS AND METHODS: Phase-contrast MR imaging was performed in 21 patients with probable idiopathic normal pressure hydrocephalus. Patients were selected for shunting on the basis of pathologically increased intracranial pressure pulsatility. Patients with shunts were offered a second MR imaging after 12 months. Ventricular volume and transverse aqueductal area were calculated, as well as clinical symptom score.RESULTS: No correlations between aqueductal stroke volume and preoperative scores of mean intracranial pressure or mean wave amplitudes were observed. Preoperative aqueductal stroke volume was not different between patients with shunts and conservatively treated patients (P = .69) but was correlated with ventricular volume (R = 0.60, P = .004) and aqueductal area (R = 0.58, P = .006) but not with the severity or duration of clinical symptoms. After shunting, aqueductal stroke volume (P = .006) and ventricular volume (P = .002) were reduced. A clinical improvement was seen in 16 of 17 patients who had shunts (94%).CONCLUSIONS: Aqueductal stroke volume does not reflect intracranial pressure pulsatility or symptom score, but rather aqueduct area and ventricular volume. The results do not support the use of aqueductal stroke volume for selecting patients for shunting.ASVaqueductal stroke volumeICPintracranial pressureiNPHidiopathic normal pressure hydrocephalusMWAmean ICP wave amplitudePCMRphase-contrast MR imaging